Development and evaluation of bivalent dna vaccine against avian infectious bronchitis - Bande, Faruku (2015)
Infectious bronchitis (IB) constitutes a major challenge to the poultry industry worldwide. The widely used live attenuated IB vaccines suffer from numerous limitations, including but not limited to, reversion to virulence, recombination and mutations. Whereas killed IB vaccines induce poor immune response and require repeated dosing. DNA vaccines on the other hands, have the potentials to induce both humoral and cell mediated immune responses against infectious pathogens with minimal unwanted effects. In this study, the S1 glycoprotein of M41 and CR88 IBV strains were selected for the development of bivalent DNA vaccine against IB. Bioinformatic analysis revealed structural and phylogenetic differences between the two virus strains. However, several conserved B-cells and T-cells epitopes were predicted to occur among these strains. To develop a broad-based DNA vaccine against the two strains, the full-length S1 glycoprotein genes of M41 and CR88 IBV strains were cloned individually as well as in combination to obtain a pBudCR88-S1, pBudM41-S1 and pBudCR88-S1/M41-S1 plasmids. In vitro expressions of the constructed IB-DNA plasmids were confirmed by immunofluorescence and RT-PCR assays 42 hrs post transfection in chicken embryo fibroblast cells. In order to improve the delivery potential of the candidate DNA vaccine plasmid and protect it from endonuclease degradation, a chitosan - saponin (CS-SP) nanoparticle was synthesized, characterized and used for the encapsulation of the bivalent IB DNA plasmids. Characterization of the CS-SP nanoparticle revealed a spherically-shaped nanoparticle with a size below 100 nm and a zeta potential of 38.9 mV. The encapsulated bivalent IB-DNA plasmid was found to be thermostable, less toxic and protected against in vitro enzymatic degradation. Subsequently, the efficacy of the candidate DNA vaccine was evaluated by immunizing 3 weeks old SPF chickens. Six groups of chickens comprising of vaccinated and control chicken received 100 μg of plasmid as follows: - PBS-control (A) empty-plasmid control, pBudCE (B); pBudM41-S1 (C); pBudCR88- S1 (D); pBudCR88-S1/M41-S1+nano (E) and pBudCR88-S1/M41-S1-without nano (F). All chickens except those in group E received two booster vaccination at two week intervals. To assess the effect of CS-SP, chickens in group E only received the first booster vaccine. To evaluate the vaccine’s protective capacity, the initial six chicken groups (A, B, C, D, E, F) were divided each into 2 parts as M41-challenged (n=6) and CR88-challenge (n=6) subgroups and then challenged accordingly with 105 EID50 of M41 and CR88 IBV strains two weeks after the last booster vaccination. All chickens were monitored before terminating the experiment two weeks after challenge. Evaluation of immune response was carried out by measuring the IBV specific antibodies (weekly); percentage CD3+, CD4+ and CD3+, CD8+ T-cells (two weeks after the last booster); clinical signs (after the challenge); oropharyngeal and cloacal virus shedding (day 3, day 5, day 10 and day 15) and histopathological lesion scores (two weeks after challenge). Analysis of humoral and cell mediated immune (CMI) response revealed a significant increase in anti-IBV antibody as well as CD3+, CD4+ and CD3+, CD8+ T cells responses in chickens vaccinated with bivalent IB-DNA vaccines as determined by ELISA and flow-cytometry respectively. Vaccinated chickens exhibited milder clinical signs following virus challenge as compared to the control groups. Furthermore, vaccination with a bivalent DNA plasmid especially the nanoencapsulated plasmid (pBudCR88-S1/M41-S1+nanoparticles) protected chickens against heterologous virus challenge as revealed by a significant reduction in the (p<0.05) in orophyrengeal and cloacal virus shedding following M41 and CR88-IBV strains. However, monovalent IB-DNA vaccines could only protect against homologous virus challenge (P<0.05). Histopathologically, lesion scores tend to be higher in the trachea and kidney of control-unvaccinated chickens (A and B) compared to the vaccinated chicken groups (C-F), although this difference was not statistically significant (p>0.05). In conclusion, this study demonstrated that bivalent DNA vaccine expressing S1 glycoproteins from M41 and CR88 IBV strains is able to induce significant humoral and CMI responses that is able to protect vaccinated chickens against challenge with both M41 and CR88 IBV serotypes. These findings highlight the potential applications of bivalent DNA vaccine as an alternative strategy for the control of infectious bronchitis in poultry.